MENINGKAKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING: IMPROVING MOTIVATION AND LEARNING OUTCOMES IN MATHEMATICS THROUGH THE APPLICATION OF A CONTEXTUAL TEACHING AND LEARNING APPROACH - Layn, Ruslan; Setyo, Arie Anang; Musa'ad, Faida; Gegetu, Usman (KAMBIK: Journal of Mathematics Education, 2024)
This study uses a contextual teaching and learning (CTL) strategy to enhance students' mathematical learning outcomes and motivation when studying flat-sided geometric material. There are four phases to the implementation of this classroom action research approach: planning, carrying out the action, observing, and reflecting. Thirty pupils in the VIII B MT class. In this study, Al-Akbar Sorong City is the focus. According to the research findings, student learning outcomes in Cycle I had an average score of 67.00, placing them in the "low" category. However, following the implementation of CTL in Cycle II, student learning outcomes dramatically improved, reaching an average score of 80.33, placing them in the "high" category. Furthermore, there was an improvement in students' motivation to learn, as evidenced by the fact that 80% of them in Cycle II received high learning motivation levels. According to this study, using CTL to teach mathematics can greatly enhance students' motivation and learning outcomes. This result is consistent with earlier research demonstrating that CTL can raise students' motivation and proficiency in mathematics instruction. This study concludes that learning results and student motivation can be effectively enhanced by applying the CTL strategy to mathematics instruction. It is advised to conduct more research to carry out more research.